Strategi Meningkatkan Minat Baca Siswa Kelas 6 melalui Pemanfaatan Pojok Baca di SDN Wonokusumo V/44 Surabaya - Ayu Anggraini (PARADIGMA: JURNAL PEMIKIRAN DAN PENELITIAN PENDIDIKAN, 2025)
This study delves into strategies to enhance the reading interest of 6th-grade students through the utilization of a reading corner at SDN Wonokusumo V/44, Surabaya, East Java. The reading corner is designed to create a stimulating learning environment outside formal class hours, providing a space for students to engage in more relaxed and interactive reading activities. The research employed various methods, including observation, interviews, questionnaires, and documentation analysis over one semester, offering a comprehensive view of the impact of the reading corner on students' reading interest. The findings reveal that the reading corner effectively boosts the reading interest of 6th-grade students. Observations highlighted active student engagement as they used the reading corner to read and discuss books, creating a more dynamic and collaborative reading experience. The questionnaire results also indicated a significant increase in the frequency of visits to the reading corner and the number of books borrowed after the program's implementation, reflecting a positive change in students' reading behavior. Teachers play a crucial role as facilitators in the success of this program. They not only guide students in selecting books that match their interests and reading levels but also integrate reading corner activities into their teaching to comprehensively develop reading skills. This approach not only enhances teacher-student interactions but also builds higher motivation among students to engage in reading activities. Full support from the school, including the principal, significantly contributes to the program's success. Both the principal and teachers are committed to creating a supportive learning environment that allows students to experience the broader benefits of reading. This research underscores the importance of a supportive learning environment in enhancing elementary students' reading habits. The implementation of the reading corner demonstrates that by providing an appealing and relevant facility, along with support from teachers and the school, students' reading interest can be significantly enhanced. Furthermore, the program encourages the overall development of students' literacy skills, including critical thinking, analytical abilities, and communication skills. These findings lay the groundwork for further development of literacy strategies in schools, particularly in leveraging informal learning spaces like reading corners to cultivate a sustainable reading culture. Future recommendations include expanding the book collection to be more diverse and relevant to students' interests and enhancing teacher training to maximize the impact of the reading corner. With these steps, the reading corner is expected to become an integral part of a broader learning strategy that not only boosts reading interest but also supports students' academic and personal development comprehensively. This study provides valuable insights for other schools to adopt and adapt similar strategies in their efforts to enhance literacy and reading interest among their students